Tecnologias em fluxo contínuo de compostos cicloeptânicos derivados da (R)-(–)-carvona e do fragmento C23-C31 usado na síntese total dos policetídeos spirangien A metil éster e spirodienal A - Alves, Leandro de Carvalho (2015)
Continuous flow technology of cycloheptanic compounds derived from (R)-(–)-carvone and the C23-C31 fragment used in the total synthesis of spirangien A methyl ester and spirodienal A polyketides” In the first part of this thesis is described the improvement and development of two synthetic routes to the cycloheptenone 73, in the deca-gram scale, from the monoterpene (R)-(–)-carvone (58). Were developed reactions in the continuous flow mode to accelerate and increase the scale production of 73, and thus avoiding chemical logistics issues. Sharing the principle of the diversity oriented synthesis and taking advantage from the cycloheptanic chiron flexibility, were developed α-carbonyl alkylations followed by catalysis with transition metal, to get, in a fast way, structurally diverse compounds such as spiro 74, guaiane type 75, xathane 76 and the tris-ketal compound 78. The second part of this thesis encompasses some results of our collaboration with Prof. Steven V. Ley CBE FRS and deals with the synthesis acceleration of the fragment 145 through the usage of continuous flow processes. The compound 145 is an advanced synthetic intermediate for the spirangien A (79), spirangien A methyl ester (80) and spirodienal A (81) syntheses, which are on matter at the Prof. Ley`s group. xxiii